Development of nanofiber facial mask inspired by the multi-function of dried ginger (Zingiberis Rhizoma) essential oil - Yiwen Hao; Xia Lin; Wenwen Liu; Tinghongyang Jiang; Xing Zhang; Shasha Yang; You Huang; Wenjing Lai; Chaomei Fu; Zhen Zhang (Scientific Reports)
Abstract Plant extracts, especially herbal extracts, are in line with the cosmetics development trend of natural and safe in today’s world. Dried ginger essential oil (DGEO) is a fragrant oily liquid extracted from the dried roots of Zingiber officinale Rosc. This research investigated DGEO could effectively inhibit Staphylococcus aureus and Propionibacterium acnes. And delay skin aging in mice by down-regulating the expression of TNF-α and the production of MMP-1. These indicates that DGEO has antibacterial and anti-aging effects, and has the potential in beauty and skin care. However, DGEO is easy to volatilize, so it is lack of stability, and the application of DGEO is greatly limited. Therefore, we aim to improve the stability of DGEO and expand its application in facial mask. To achieve this, DGEO was firstly complexed with the β-cyclodextrin (β-CD) to prepare DGEO-β-CD-IC. Then, electrospinning was used to make DGEO-βCD-IC into a nanofiber facial mask. In this process, we found that the thermal stability of DGEO-βCD-IC was significantly improved, and the degradation process was slower than that of physical mixture. During the preparation of the nanofiber mask, DGEO did not undergo a chemical reaction. And the fibers of facial mask were evenly distributed, with smooth surfaces and tight structures. Its diameter was between 90 and 110 nm. And the facial mask had good hydrophilic performance and moisturizing efficacy. It could increase the skin water content by 47.82% on average. What’s more, the safety tests showed that the facial mask was mild and safe. These results show that we improve the stability of DGEO and successfully develop a promising application prospects nanofiber mask. This work may enrich the use of herbal extracts in skincare products.